2014
DOI: 10.1158/2159-8290.cd-13-0915
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the Linear Ubiquitin Chain Assembly Complex in Lymphoma Revealed by Rare Germline Polymorphisms

Abstract: Constitutive activation of NF-κB is a hallmark of the activated B cell-like (ABC) subtype of diffuse large B cell lymphoma (DLBCL), owing to upstream signals from the B cell receptor (BCR) and MyD88 pathways. The linear polyubiquitin chain assembly complex (LUBAC) attaches linear polyubiquitin chains to IκB kinase γ, a necessary event in some pathways that engage NF-κB. Two germ line polymorphisms affecting the LUBAC subunit RNF31 are rare among healthy individuals (~1%) but enriched in ABC DLBCL (7.8%). These… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
184
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 134 publications
(187 citation statements)
references
References 51 publications
(86 reference statements)
2
184
0
Order By: Relevance
“…This complex catalyzes linear ubiquitylation and participates in multiple signaling pathways converging on NF-κB (Iwai et al, 2014). Although the LUBAC is a central part of the CBM needed for IKK activation in lymphocytes and in ABC DLBCL cells, the exact role of HOIL1 remains elusive (Dubois et al, 2014;Yang et al, 2014). We now report that HOIL1 is a substrate of MALT1 that is cleaved in TCR-stimulated cells and in ABC DLBCL cells, and that this processing contributes to the optimal activation of NF-κB in lymphocytes.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…This complex catalyzes linear ubiquitylation and participates in multiple signaling pathways converging on NF-κB (Iwai et al, 2014). Although the LUBAC is a central part of the CBM needed for IKK activation in lymphocytes and in ABC DLBCL cells, the exact role of HOIL1 remains elusive (Dubois et al, 2014;Yang et al, 2014). We now report that HOIL1 is a substrate of MALT1 that is cleaved in TCR-stimulated cells and in ABC DLBCL cells, and that this processing contributes to the optimal activation of NF-κB in lymphocytes.…”
Section: Introductionmentioning
confidence: 86%
“…We also provide evidence that exacerbated MALT1 activity in ABC DLBCL cells results in the constitutive cleavage of HOIL1. In addition to interfering with the LUBAC stability (Yang et al, 2014), targeting HOIL1 cleavage might therefore offer a new angle for therapeutic targeting in ABC DLBCL. How exactly HOIL1 exerts its negative function remains unclear.…”
Section: Hoil1mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent analyses showed that LUBAC is essential for the growth of ABC DLBCL cells through suppression of NF-κB activity. Moreover, two rare SNPs in the HOIP gene are enriched in ABC DLBCL [ 21 ]. We have also observed that attenuation of LUBAC suppressed lung metastases of osteosarcomas in mice [ 22 ].…”
Section: Perspectivesmentioning
confidence: 51%
“…Aberrant NF-κB activation plays an essential role in the pathogenesis of activated B cell-like diffuse large B cell lymphomas (ABC DLBCL) [ 21 ]. Recent analyses showed that LUBAC is essential for the growth of ABC DLBCL cells through suppression of NF-κB activity.…”
Section: Perspectivesmentioning
confidence: 99%